Job tenure : does history matter? - Booth, Alison L. [Verfasser]; Francesconi, Marco [Verfasser]; Garcia-Serrano, Carlos [Verfasser] (My University, 1997)
"This paper uses the retrospective work history data from the British Household Panel Survey to examine patterns of job mobility and job tenure for men and women over the twentieth century. British men and women hold an average of five jobs over their lifetimes, and one-half of all lifetime job changes occur in the first ten years. For both men and women, the separation hazard is increasing in the first few months of a job, and declines thereafter. History is found to affect job tenure in two important respects. Individuals entering the labour market earlier in the twentieth century are characterized by different tenure patterns than later cohorts: job tenure is typically longer for earlier cohorts, and there are more pronounced gender differences. Individual history also matters: job accumulation is assiciated with longer job tenure and, as jobs accumulate, women are more likely to shift into part-time employment while men are more likely to shift into self-employment." (author's abstract, IAB-Doku) ((en)) Anhand von Panel-Daten untersuchen die Autoren die berufliche bzw. zwischenbetriebliche Mobilität im Lebenszyklus in Grossbritannien und ihre Entwicklung zwischen 1900 und 1990. (IAB)
Keywords: G 1.3.3.3 Mobilität; G 2.3.1 Arbeitsteilung & -organisation; T 3.5 Statistik; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; I 2.2.1 Westeuropa; Zwischenbetriebliche Mobilität; Berufliche Mobilität; Längsschnittuntersuchung; Berufsverlauf; Quantitative Angaben; Großbritannien; 1990-1990